Addressing Long-Standing Questions with Advanced Approaches: The 4th B Chromosome Conference - Martins, Cesar [UNESP]; Trifonov, Vladimir; Houben, Andreas (Karger, 2020)
B chromosomes (Bs) are enigmatic accessory genomic elements extensively characterized in diverse eukaryotes. Since their discovery in the beginning of the 20th century, B chromosomes have been the subject of investigation in laboratories all around the world. As a consequence, scientific meetings have dealt with B chromosomes, including the most specific and important conference in the field, The B Chromosome Conference. The 4th B Chromosome Conference (4BCC) took place in Botucatu, Brazil, in 2019 and was an excellent opportunity to discuss the latest developments in the B chromosome research field. B chromosome science has advanced from classical and molecular cytogenetics to genomics and bioinformatics approaches. The recent advances in next-generation sequencing technologies and high-throughput molecular biology protocols have led Bs to be the subject of massive data analysis, thus enabling the investigation of structural and functional issues not considered before. Although extensive progress has been made, questions are still remaining to be answered. The advances in functional studies based on RNA, epigenetics, and gene ontologies open the perspective to a better understanding of the complex biology of B chromosomes.
Keywords: Accessory chromosome; Chromosome rearrangement; Drive; Evolution; Genome; Karyotype; Selfish chromosome